Phytoplankton shifts in the Central Bohai Sea over the last 250 years reflect eutrophication and input from the Yellow River - Lei Li (Elsevier, 2021)
Phytoplankton shifts driven by the environmental changes can significantly impact the functioning of marine ecosystems. Analyzing time series data is an important way to understand how phytoplankton responds to environmental changes. Here, multiple indicators, including diatoms and dinoflagellate cysts, total organic matter, carbon and nitrogen isotopes, and biosilicate, were analyzed in the sediment core from the Central Bohai Sea. A 250-year palaeo-environment was reconstructed based on these indicators to examine the responses of phytoplankton assemblages to environmental events. Two significant shifting points were identified from the varying trend of diatoms and cysts. The first one occurred in the 1850s, when the Yellow River outlet relocated from the southern Yellow Sea to the Bohai Sea, as evidenced by finer grain size and lower sea salinity, causing a significant increase in total biomass and brackish species. The other shift happened in the 1970s, when significantly increased fertilizer usage and wastewater discharge led to more organic matter in the core and nitrogen enrichment in the water column up to the 2010s, causing a marked increase in total biomass, small-sized species, and harmful algal bloom species. Redundancy analysis between major community shifts and environmental factors indicated that the Yellow River input and nutrient enrichment had a more important role in regulating phytoplankton shifts than rising temperature after the 1970s.